MICROBIOLOGICAL PROCESSES TAKE PLACE IN THE SOIL DURING THE MAIN TILLAGE AFTER WINTER WHEAT IN DIFFERENT PERIODS AND METHODS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
After the autumn wheat harvest, a significant increase in soil agrochemical properties and microbiological activity was observed when plowing at 28-30 cm depth in the fall after plowing at 28-30 cm depth and cultivating a repeat crop in the summer. Microbiological high activity (ammonifiers, spore-forming, oligonitophils, actinomycetes) in the topsoil is explained by the fact that, firstly, the root and root remnants treatment , and secondly, the secondary crops planting has a positive effect on soil overall properties. Microorganisms in-depth study found in the soil is one of the most pressing issues for today, increasing soil fertility and productivity and obtaining quality and abundant yields. Because it is impossible to make the soil fertile and fertile without a deep understanding of the irrigated soils biology, without studying the microbiological processes that take place in it [2]. A.L. Toropkina [3] in her study explained that the microbiological rhythm of gray soils is related to the agrotechnical measures effect carried out during the cotton cultivation . One of the important indicators of soil biological activity is its ability to break down cellulose, compared with tillage in a 0-30 cm alkaline black soil layer in general, the flax stem breakdown was greater during plowing than on surface tillage. In the lower layers of the surface treated soil, the mineralization processes are reduced in the uncultivated layers, which indicates that the energy of CO2 emission and nitrification process is weakened. [4]. The soil water-physical, agrochemical and microbiological properties deterioration with the increase in volume weight has been reflected in the scientific work of a number of foreign scientists. [5-6].